MUSIK SEBAGAI MEDIA DAKWAH DALAM PEMBERDAYAAN SISWA TUNA GRAHITA NIPOTOWE PALU - Nawir, Mohammad; Hidayat, Mokh. Ulil; Iskandar, Iskandar (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi, 2016)
This paper deals with the use of music as media of preaching in empowering the students of Tuna Grahita Nipotowe Palu. The questions are what kind of music is it? How to use music as media of preaching? The result showed that music as media of preaching has great benefits for the students. The benefits include making them comfortable, motivated, cheerful, and happy. Music makes them active in every activities given by the instructor. Music also improves their memories and influences their psychology. Furthermore, music helps to empower the students, makes them have effective communication, and can be made as therapy for the students.